Analysis of the Application of the Total Physical Response Method in Improving Arabic Kalam Skills - Bagus Siyam Prasetya; Muhamad Bisri Ihwan (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Kalam skills remain a significant challenge in learning Arabic, particularly in Islamic boarding schools that employ traditional and less communicative approaches. This study aims to evaluate the implementation and effectiveness of the Total Physical Response (TPR) method in enhancing students' kalam skills at Madrasah Diniyah Roudlotutholibin in Banyuwangi. Utilizing a qualitative method with a case study approach, data were collected through observations, interviews, and documentation, and analyzed using interactive qualitative techniques, including data reduction, data presentation, and conclusions. The results indicate that the application of the TPR method effectively improves students' kalam skill by increasing fluency, language accuracy, vocabulary richness, response speed, and verbal participation. The implementation of the TPR method is through comprehension phase, physical action, and speech production strategy. Among the factors that support the effectiveness of TPR implementation are the readiness of some students, who demonstrate high interest and enthusiasm for learning, as well as the courage to attempt speaking. This is further enhanced by a conducive Islamic boarding school environment, engaging activity programs, and active, competent teachers. In contrast, the inhibiting factors include the diverse backgrounds of students, limited learning time, and restricted access to technology. This suggests that TPR is not merely a kinesthetic method but also a communicative approach. Therefore, it is recommended that the TPR method be further developed in the context of Arabic language learning, especially in Islamic schools still dominated by traditional methods. Abstrak Keterampilan berbicara (kalam) masih menjadi tantangan umum dalam pembelajaran bahasa Arab terutama di kalangan pondok pesantren yang masih menggunakan pendekatan tradisional dan kurang komunikatif. Penelitian ini bertujuan untuk mengevaluasi implementasi serta efektivitas metode Total Physical Response (TPR) dalam meningkatkan maharah kalam siswa di Madrasah Diniyah Roudlotutholibin Banyuwangi. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dan dianalisis dengan teknik kualitatif interaktif meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan metode TPR secara efektif meningkatkan maharah kalam siswa melalui peningkatan kelancaran berbicara, ketepatan bahasa, kekayaan kosakata, kecepatan tanggapan serta partisipasi verbal. TPR diimplementasikan melalui tahap pemahaman, tindakan fisik, dan produksi tuturan. Di antara faktor pendukung pelaksanaan TPR adalah kesiapan sebagian santri yang mempunyai minat yang tinggi dalam pembelajaran dan keberanian mencoba berbicara, lingkungan pesantren yang kondusif, program kegiatan yang memadai, dan guru yang aktif dan kompeten. Sedangkan faktor penghambat di antaranya latar belakang santri yang beragam, terbatasnya waktu pembelajaran, dan keterbatasan teknologi. Hal ini berimplikasi bahwa TPR bukan sekadar metode kinestetik, melainkan pendekatan yang komunikatif sehingga disarankan agar metode TPR terus dikembangkan dalam konteks pembelajaran bahasa Arab, khususnya di madrasah diniyah yang masih dominan dengan metode tradisional.